Characteristics of the exclusion discourse in the parliamentary debate on LGBT rights - Polkowska, Laura (Papers in Linguistics, 2024)
The study aims to define the discourse of exclusion in reference to a review of the literature on unethical communication. The undertaken analysis concerns the Polish parliamentary debate on LGBT rights as an example of the discourse of exclusion. The debate at its core aimed at reducing non-heterosexual people to their sexuality. They were also portrayed as the prototypical Other who endangers the “normal” value system and does not deserve civil rights or equal treatment.